Peran Keterampilan Mengelola Kelas dalam Meningkatkan Minat Belajar Siswa - Evi Maylitha; Marsanda Claudia Parameswara; Mochammad Fahmi Iskandar; Muhammad Farhan Nurdiansyah; Shofi Nurul Hikmah; Prihantini Prihantini (Departement of Mathematics Education, 2023)
In the learning process, teachers must formulate learning components including classroom management. In the learning process, it is often found that students are less interested in learning. For this reason, good classroom management by the teacher is needed because good classroom management can have a positive impact on the learning process. This study aims to determine the role of teacher skills in managing the class to increase students' interest in learning. In this study we used a qualitative method, namely through interviews which were reinforced by literature studies. With this research we know how the role of classroom management in increasing student interest, factors and strategies in classroom management, and the obstacles. In line with the results of his research, classroom management has a crucial role in increasing student interest in learning with various strategies carried out by the teacher to manage the class so as to foster interest in learning in students.